Double magnetic tunnel junction two bit memory and nonvolatile logic for in situ computing. (January 2023) - Qoutb, Abdelrahman G.; Friedman, Eby G.
Abstract: In exascale computing, a huge amount of data is processed in real-time. Conventional CMOS-based computing paradigms follow the read, compute, and write back mechanism. This approach consumes significant power and time to compute and store data. in situ computation – where data are processed within the memory system – is considered a platform for exascale computation. Spin transfer torque perpendicular magnetic tunnel junctions (PMTJ) is a nonvolatile memory device with several potential advantages (fast read/write, high endurance, and CMOS compatibility) to become a next generation memory solution. A double magnetic tunnel junction (DMTJ) consists of two PMTJs constructed in a vertical arrangement. In this paper, DMTJ offers the possibility of constructing not only standalone and embedded RAM but also MTJ-based VLSI computing. A DMTJ-based two bit memory cell that supports a nonvolatile logic compute paradigm is presented. The multi-level cell supports both a high speed read/write two bit memory cell and a nonvolatile logic gate that computes and stores input data in real-time.